Valence electron correlation energy embracing the diamond-lattice materials C through Sn - March, Norman H.; Rubio, Angel (Universiti Malaysia Perlis, 2008)
Link to publisher's homepage at http://www.unimap.edu.my/ ; Open access only applicable for vol. 1; issue 1, 2008.